Projection Methods for a System of Nonlinear Mixed Variational Inequalities in Banach Spaces. (15th May 2014) - Wang, Zhong-Bao; Tang, Guo-Ji; Zhang, Hong-Ling
Abstract : The existence and uniqueness of solution for a system of nonlinear mixed variational inequality in Banach spaces is given firstly. A Mann iterative sequences with errors for this system of nonlinear mixed variational inequalities in Banach spaces is studied, by using the generalized f -projection operatorπ K f . Our results extend the main results in (Verma (2005); Verma (2001)) from Hilbert spaces to Banach spaces.